Supplementation of L-carnitine and paylean improve growth performance of pigs in a commercial finishing facility - James, B.W.; Owen, K.Q.; Woodworth, J.C.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Our previous experiments evaluating the interactive effects of dietary L-carnitine and Paylean have primarily focused on improved meat quality benefits of feeding carnitine in combination with Paylean. Although there were numeric trends for improved growth performance in the previous experiments conducted at university facilities, the responses were not statistically significant. A recent study conducted in a commercial finishing facility demonstrated improved growth performance in pigs fed carnitine for the 4-week period prior to slaughter. The cause for the growth response observed in the commercial facility compared to the two previous studies conducted at a university research facility may have been related to feed intake, stress, or the larger sample size compared to the first studies. In addition, pigs in the commercial facility study were fed carnitine from 97 lb until slaughter. Therefore, the objectives of this experiment were to confirm the growth performance results of the previous trial in a commercial finishing facility and to evaluate the interactive effect of L-carnitine and Paylean on growth performance and carcass characteristics when supplemented for only 3 weeks prior to slaughter.
Keywords: Swine; Carnitine; Paylean; Carcass characteristics